2017
DOI: 10.1515/revecp-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of SME Finance: Evidence from Three Central European Countries

Abstract: This paper explores the determinants of access to finance for small and medium enterprises (SMEs) in the context of three Central European countries: Czech Republic, Slovak Republic, and Hungary. The data set of the research is obtained from the BEEPS survey, which is conducted by the World Bank and the European Bank for Reconstruction and Development. This paper empirically analyses firms not only from the SMEs point of view, but also shows results for micro, small and medium enterprises separately. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
(66 reference statements)
3
23
0
Order By: Relevance
“…Reasons are related to financial risks as well as access to foreign sources of financing. This corresponds to the results of the analysis Rahman et al (2017), who found that not only small but also short-term firms are more vulnerable to limited access to bank finance. That limited access is linked to the risk of default, which also affects interest rates.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Reasons are related to financial risks as well as access to foreign sources of financing. This corresponds to the results of the analysis Rahman et al (2017), who found that not only small but also short-term firms are more vulnerable to limited access to bank finance. That limited access is linked to the risk of default, which also affects interest rates.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates some gender discrimination in the credit market within advanced European countries (e.g. in Felicio & Galindo Villardón, 2015) In the case of medium-sized companies, it has been confirmed that innovative businesses have received more loans from banks (Rahman et al, 2017;Tvaronavičienė, 2016). The economic position of SMEs in countries is gradually increasing.…”
Section: Overview Of Research Studiesmentioning
confidence: 93%
See 3 more Smart Citations